Reorientation of Andragogy Theor - Roy Bagaskara (STKIP ROKANIA, 2019)
The purpose of writing this article is to reintroduce the concept of adult learning (andragogy). Because basically learning adults with children is different. It is said by adults, when physically, biologically, and psychologically mature. The method of writing this article uses the literature study method. Knowles explained that andragogy is an art of teaching for adults. According to Knowles there are four main assumptions that distinguish between andragogy and pedagogy, namely: self-concept, experience, readiness for learning, and orientation towards learning activities. The application into the learning process is to create a pleasant learning atmosphere, pleasant physical environment. Identification of the needs of learning citizens is identified together between learning citizens and tutors so that it can be known the real situation. Fourth, learning experiences are arranged together between learning citizens and tutors so that they will feel ownership of the material to be delivered. Keywords: Reorientation, Learning, Andragogy